Improving therapeutic efficacy of voriconazole against fungal keratitis: Thermo-sensitive in situ gels as ophthalmic drug carriers - Üstündağ Okur, Neslihan; Yozgatlı, Vildan; Okur, Mehmet Evren; Yoltaş, Ayşegül; Siafaka, Panoraia, I. (Elsevier Science Bv, 2019)
The aim of this research was to evaluate the potential use of in situ gel formulations for voriconazole ocular delivery as fungal keratitis treatment. The in situ gelling system was applied to increase residence time and the bioavailability of voriconazole in the ocular mucosa. Temperature-triggered in situ gel formulations were prepared by cold method. Poloxamer 188, poloxamer 407 and carboxymethylcellulose were used for the preparation of thermosensitive in situ ocular gel. Voriconazole concentration in formulations was 0.1% (w/w). The prepared gels were evaluated for clarity, sol-gel transition temperature, gelling capacity, pH, viscosity, FT-IR and drug content. The gelation temperatures of all the formulations were within the range of 29-34 degrees C. All formulations exhibited fairly uniform drug content. Furthermore, sterility, antifungal activity, stability, in vitro drug release, ex vivo permeation, and penetration and in vivo study of these formulations were also examined. Drug release results indicated that all formulations showed sustained release properties. Irritation studies showed that no ocular damage or clinically abnormal signs were observed in the cornea, conjunctiva or iris upon administration of the formulation. In conclusion, voriconazole loaded in situ gels could be offered as a promising strategy as ocular carriers for the treatment of fungal keratitis.
WOS: 000457344000037
Keywords: Voriconazole; Thermo-Sensitive in Situ Gel; Ocular Drug Delivery; Microbiological Study; Ex Vivo; Rabbit; Ocular Irritation Test